PELATIHAN PEMANFAATAN BARANG BEKAS SEBAGAI MEDIA STIMULASI INTEGRATIF PADA GURU PAUD DAN KADER PKK DI JATINEGARAKAUM - Kabbaro, Hurriyyatun; Oktaviani, Maya; Elmanora; Nafisah, Nada; Anggun Rakhmawati, Tri; Dwi Rahmadina, Annisa (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
The Kacintaan Program (Kampung Cinta Lingkungan) is an Environmental-themed Integrative Stimulation Education Program for Early Childhood Education (PAUD) Teachers and Family Welfare Empowerment Cadres (PKK). This activity also aims to improve the skills of families and Early Childhood Education (PAUD) teachers in utilizing used goods into useful products. As well as, improving the skills of families and early childhood education (PAUD) teachers in utilizing used goods as an integrative stimulation medium for early childhood. The method in this program is PAR (Participatory Action Research). Program participants involved 27 PAUD teachers and PKK cadres at RPTRA Jaka Berseri, Jatidera Kaum. This program was carried out on August 9-10, 2022. The results of the implementation of this activity program showed that all participants could know and had applied the three morals, it could be seen that participants in these activities had instilled and taught the value of environmental love in the scope of Jatinegara Kaum based on indicators of the character of love. This environment and activity is very beneficial for PKK Cadres and PAUD teachers within the scope of RPTRA Jaka Berseri, Jatinegara Kaum, East Jakarta